2017
DOI: 10.1126/science.aaf4557
|View full text |Cite
|
Sign up to set email alerts
|

Design of a synthetic yeast genome

Abstract: We describe complete design of a synthetic eukaryotic genome, Sc2.0, a highly modified Saccharomyces cerevisiae genome reduced in size by nearly 8%, with 1.1 megabases of the synthetic genome deleted, inserted, or altered. Sc2.0 chromosome design was implemented with BioStudio, an open-source framework developed for eukaryotic genome design, which coordinates design modifications from nucleotide to genome scales and enforces version control to systematically track edits. To achieve complete Sc2.0 genome synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
467
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 517 publications
(477 citation statements)
references
References 42 publications
3
467
0
7
Order By: Relevance
“…An "endoreduplication backcross" strategy was applied to distinguish these possibilities (fig. S10 and tables S2 to S4) (24). This revealed that the large-scale duplications at positions 291,217-299,980 bp and 305,355-325,235 bp were readily outcrossed, and we concluded that they must have integrated into locations on another chromosome(s) (fig.…”
Section: Characterization Of Synvmentioning
confidence: 94%
“…An "endoreduplication backcross" strategy was applied to distinguish these possibilities (fig. S10 and tables S2 to S4) (24). This revealed that the large-scale duplications at positions 291,217-299,980 bp and 305,355-325,235 bp were readily outcrossed, and we concluded that they must have integrated into locations on another chromosome(s) (fig.…”
Section: Characterization Of Synvmentioning
confidence: 94%
“…Upon completion, the Sc2.0 strain will be world's first eukaryote with a streamlined chemicallysynthesised genome. In addition to the removal of repetitive sequences, liberation of a codon and the introduction of hundreds of watermark sequences, LoxPsym sequences were introduced at the 5'-ends of all genes considered individually non-essential [22,23]. These sites allow for inducible homologous recombination downstream of all non-essential genes, mediated by the action of the site-specific Cre-recombinase.…”
Section: Yeast As a Recombinant Host For Bioflavour Productionmentioning
confidence: 99%
“…Upon completion, the Sc2.0 strain will be world's first eukaryote with a streamlined chemically-synthesised genome. In addition to the removal of repetitive sequences, the liberation of a codon and the introduction of hundreds of watermark sequences, LoxPsym sequences were introduced at the 5 -ends of all genes considered individually non-essential [22,23]. These sites allow for inducible homologous recombination downstream of all non-essential genes, mediated by the action of the site-specific Cre-recombinase.…”
Section: Introductionmentioning
confidence: 99%